Ex vivo Detection and Characterization of Hepatitis B Virus-Specific CD8+ T Cells in Patients Considered Immune Tolerant - Sung, Pil Soo; Park, Dong Jun; Kim, Jung-Hee; Han, Ji Won; Lee, Eun Byul; Lee, Gil Won; Nam, Hee Chul; Jang, Jeong Won; Bae, Si Hyun; Choi, Jong Young; Shin, Eui-Cheol; Park, Su-Hyung; et al. (Frontiers in Immunology, 2019)
In this study, we aimed to detect and characterize ex vivo virus-specific CD8+ T cells in patients with immune-tolerant hepatitis B virus (HBV) infection. We investigated a Korean chronic hepatitis B cohort composed of 15 patients in the immune-tolerant phase, 17 in the immune-active phase, and 13 under antiviral treatment. We performed enzyme-linked immunospot (ELISpot) assays ex vivo and intracellular cytokine staining after in vitro culture. We also performed ex vivo multimer staining assays and examined the expression of programmed death-1 (PD-1) and CD127 in pentamer-positive cells. Ex vivo ELISpot revealed that HBV-specific T cell function was weaker in immune-tolerant patients than in those under antiviral treatment. In vitro culture of peripheral blood mononuclear cells for 10 days revealed that HBV-specific CD8+ T cells produced interferon-γ in some immune-tolerant patients. We detected HBV-specific CD8+ T cells ex vivo (using the HBV core18-27 pentamer) in patients from all three groups. The PD-1+ subset of pentamer+ CD8+ T cells was smaller ex vivo in the immune-tolerant phase than in the immune-active phase or under antiviral treatment. Interestingly, the proportion of PD-1+ CD8+ T cells in HBV-specific CD8+ T cells correlated with patient age when all enrolled patients were analyzed. Overall, HBV-specific CD8+ T cells are present in patients considered as immune-tolerant, although their ex vivo functionality is significantly weaker than that in patients under antiviral treatment (P < 0.05). Despite the high viral load, the proportion of PD-1 expression in HBV-specific CD8+ T cells is lower in the immune-tolerant phase than in other phases. Our results indicate appropriate stimulation may enhance the effector function of HBV-specific CD8+ T cells in patients considered as being in the immune-tolerant phase.